Does transcutaneous electrical nerve stimulation affect pain, neuropathic pain, and sympathetic skin responses in the treatment of chronic low back pain? A randomized, placebo-controlled study - Yaksi, Elif; Ketenci, Aysegul; Baslo, Mehmet Baris; Orhan, Elif Kocasoy (The Korean journal of pain, 2021)
Background: The purpose of this study was to assess the effectiveness of transcutaneous electrical nerve stimulation (TENS) in chronic low back pain and neuropathic pain. Methods: Seventy-four patients aged 18-65 with chronic low back pain were included in the study. Baseline measurements were performed, and patients were randomized into three groups. The first group received burst TENS (bTENS), the second group conventional TENS (cTENS), and the third group placebo TENS (pTENS), all over 15 sessions. Patients’ visual analogue scale (VAS) scores were evaluated before treatment (preT), immediately after treatment (postT), and in the third month after treatment (postT3). Douleur Neuropathique 4 Questions (DN4), the Modified Oswestry Low Back Pain Disability Questionnaire (MOS), the Beck Depression Inventory (BDI), and sympathetic skin response (SSR) values were also evaluated preT and postT3. Results: A statistically significant improvement was observed in mean VAS scores postT compared to preT in all three groups. Intergroup comparison revealed a significant difference between preT and postT values, that difference being assessed in favor of bTENS at multiple comparison analysis. Although significant improvement was determined in neuropathic pain DN4 scores measured at postT3 compared to preT in all groups, there was no significant difference between the groups. No statistically significant difference was also observed between the groups in terms of MOS, BDI, or SSR values at postT3 (P > 0.05). Conclusions: bTENS therapy in patients with low back pain is an effective and safe method that can be employed in short-term pain control.